(3QSGdI aj JMbjb ShA GdeRGLs - (3YjSi Hf jMji GdeSjMj GdLQLGfj, CHh Sgd , J (B401 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf bGd CHh Sgd CeQfi GdCejQ NhGQRe TGg Cf CUfa cJGHkG CHMK ajg Yf ShA GdeRGL eGgh hce CUfGag s
(3BNQgG (B:s
(3Ef ShA eRGL GdYVh gh HYV CUfGa CeQ CNjg hGdPi hLH Cf fPcQ ai gPG GdcJGH agh GdPi ChQOfGg Je GdcJGH HYhf Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGdKIs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B110 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B35s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs